Creative Economic Opportunities Based on Local Culture in Banyuwangi: Peluang Ekonomi Kreatif Berbasis Budaya Lokal di Banyuwangi - Agus Mursidi; Dhalia Soetopo (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Local culture-based creative economy has become an important pillar in economic development in various regions, including Banyuwangi. With cultural richness such as Gandrung dance, Osing batik, and various cultural festivals, Banyuwangi has great potential to develop a sustainable creative economy. This study aims to analyze the opportunities, challenges, and sustainability strategies in developing a local culture-based creative economy. The method used was a seminar involving 50 participants from various groups, including creative economy actors, academics, and local MSMEs. The results of the seminar showed that digitalization and product innovation are the main factors in increasing the competitiveness of the creative economy in Banyuwangi. In addition, there are challenges in the form of a lack of digital literacy, limited access to capital, and the need for protection of Intellectual Property Rights (IPR) for local cultural products. To overcome these challenges, the proposed sustainability strategies include increasing training and education for creative economy actors, strengthening digital infrastructure, and diversifying funding through partnerships with the private sector and government. With the implementation of the right strategy, the local culture-based creative economy in Banyuwangi can continue to develop as a leading sector that not only supports regional economic growth but also preserves local cultural heritage.